Oil and gold return spillover and stock market elasticity during COVID-19 pandemic: A comparative study between the stock markets of oil-exporting countries and oil-importing countries in the Middle East - Bani-Khalaf, Omar; Taspinar, Nigar (Elsevier Sci Ltd, 2022)
This article aimed to study the return spillover effect of oil and gold on the elasticity of financial markets in a group of countries in the Middle East. The results showed a heterogeneous impact of oil and gold returns on the stock market's elasticity. In contrast, oil returns significantly affected elasticity in most oil-exporting countries. Additionally, the elasticity of financial markets in oil-importing countries showed a slight impact on the movement of oil returns. The impact of oil and gold returns also varied among short, medium, and long-term periods; gold returns were greater for Kuwait, Bahrain, Saudi Arabia, and Jordan. The impact of oil was more in Qatar, Bahrain, and Egypt, whereas the effect of gold and oil was equal in Turkey. Last, the effect of the COVID-19 pandemic on the elasticity of financial markets was significant.
Keywords: Oil prices; Gold price; Stock market elasticity; COVID-19; Wavelet coherence test; Partial wavelet coherence test